EFEKTIVITAS KACANG HIJAU DAN MADU UNTUK MENINGKATKAN HEMOGLOBIN PADA IBU HAMIL - Madiha Aini Raihan Asmawi; Damayanty; Riszanaya Mukti; Eriyanti Siregar (JOMIS (Journal of Midwifery Science), 2026)
Background: Anemia in pregnancy remains a major health problem because it increases the risk of complications for both mother and fetus. This study aimed to determine the effectiveness of mung bean and honey cookies in improving hemoglobin (Hb) levels and anemia status among pregnant women at Medan Johor Primary Health Center, Medan, North Sumatra, Indonesia, in 2026.Methods: A quantitative quasi-experimental study with a two-group pretest–posttest design was conducted. Hemoglobin levels were measured before and after the intervention. Univariate analysis described respondent characteristics and anemia status, while the Chi-square test was used for bivariate analysis with a significance level of 95% (α = 0.05).Results: Before the intervention, there was no significant difference in anemia status between the intervention and control groups (p = 0.490). After the intervention, a significant difference was found (p = 0.002). Most participants in the intervention group were no longer anemic, while mild and moderate anemia remained in the control group.Conclusion: Mung bean and honey cookies were effective in increasing hemoglobin levels and improving anemia status in pregnant women. These findings suggest that the cookies may serve as a supportive nutritional intervention for preventing and managing anemia during pregnancy.